Impact Des Arbres Associés Sur L’exploitation Cacaoyère Dans Les Zones De Transition ForêtSavane : Cas De M’Brimbo (Centre-Sud De La Côte d’Ivoire) - Jérémie, Gala Bi Trazié; Yves, Bohoussou N’Dri; Faustin, Akotto Odi; Albert, Yao-Kouamé (European Scientific Journal, ESJ, 2017)
Despite its status as the first world’s cocoa producer, the cocoa production system in Côte d’Ivoire remains characterized by low yields. To solve this problem, a study was carried out on the cocoa farms of the Agricultural Society of Bandama, in southern center of Côte d’Ivoire, in the forest and savannah transition zone. It focused on determining the impact of associated forest species in cocoa farms on cocoa tree development. Thus, the associated tree species have been inventoried. The number of associated species per hectare allowed classification of the cocoa farm according to the degree of shade. From o to more than 80 trees / ha, rates of parasitic attack and mortality increase, while yield of cocoa bean decreases. For cocoa trees at the beginning of maximum yield stage (8 years old plantation), the full-sun system is more productive, with 498 kg of cocoa beans / ha. For the highest density of associated forestspecies, the yield was 127 kg / ha, with a cocoa plant success rate of 55% and a parasitic attack rate of 40%. Moreover, the parasitic attack rate of less than 20%, due to the associated trees, could lead to a reduction of almost half of the potential yield. To avoid a fall in yield and maintain the success rate at an acceptable level, in shade systems, a threshold of 25 to 30 associated trees / ha has been established. But the parasitic attacks, responsible for the drop in yield should be controlled.